Intrinsically cell-penetrating multivalent and multitargeting ligands for myotonic dystrophy type 1 - Lee, JuYeon (Proc Natl Acad Sci U S A, 2019)
Developing highly active, multivalent ligands as therapeutic agents is challenging because of delivery issues, limited cell permeability, and toxicity. Here, we report intrinsically cell-penetrating multivalent ligands that target the trinucleotide repeat DNA and RNA in myotonic dystrophy type 1 (DM1), interrupting the disease progression in two ways. The oligomeric ligands are designed based on the repetitive structure of the target with recognition moieties alternating with bisamidinium groove binders to provide an amphiphilic and polycationic structure, mimicking cell-penetrating peptides. Multiple biological studies suggested the success of our multivalency strategy. The designed oligomers maintained cell permeability and exhibited no apparent toxicity both in cells and in mice at working concentrations. Furthermore, the oligomers showed important activities in DM1 cells and in a DM1 liver mouse model, reducing or eliminating prominent DM1 features. Phenotypic recovery of the climbing defect in adult DM1 Drosophila was also observed. This design strategy should be applicable to other repeat expansion diseases and more generally to DNA/RNA-targeted therapeutics.